Air pollution assessment using hierarchical fuzzy inference systems - Hájek, Petr; Olej, Vladimír (Univerzita Pardubice, 2009)
The paper presents the current state of air pollution assessment. Air pollution is currently realized by air pollution indices and air stress indices. However, these approaches have some limitations which can be eliminated e.g. using systems based on fuzzy logic. Therefore, we design a hierarchical fuzzy inference system for air pollution assessment using data from Pardubice micro region.
Keywords: air pollution; air quality; fuzzy logic; hierarchical fuzzy inference systems